PERITONEAL DIALYSIS TEACHING SERIES WHAT COMES OUT – HAS TO GO IN - Ishwarya Annamalai; Rajeevalochana Parthasarathy; Sukanya Govindan; Deepak Kumar S (Indian Journal of Kidney Diseases)
Hernia is one of the mechanical complication of peritoneal dialysis and is the Achille's heel. Undetected hernias prior to initiating PD and those developing after initiation can lead to complications, infection and failure of therapy. In this first article of the PD teaching series, we aim to cover the various aspects of hernia management in peritoneal dialysis.